Antioxidant Activities and Phenolic Profile of Senna alexandrina: Phenolic Profile of Senna alexandrina (Biological Sciences - PJSIR, 2025)
The purpose of the present study was to evaluate and compare the antioxidant activities of Senna alexandrina leaves as well to determine its phenolic profile. The antioxidant activity was analyzed by in vitro lipid peroxidation assay, DPPH radical scavenging activity, ABTS assay, antioxidant potential assay and metal chelation assay. The extract showed remarkable scavenging activities (58% in DPPH and 68% in ABTS assay respectively), iron chelation (60%), reduction potential (68%). The extract reduced the lipid peroxidation against FeSO4 (60%) and sodium nitroprusside (50%) in phospholipid homogenate extracted from egg yolk. HPLC analysis revealed the presence of quercetin, pyrogallol and gallic acid in leaves extract. On the basis of these results it is concluded that leaves extract of S. alexandrina are rich source of antioxidants and contain important phytochemicals.